Disease severity and muscular strength as predictors of arm and leg ergometry capacity in chronic respiratory disease. (3rd June 2016) - Chapman, Kylie Christine; Dreyer, Lukas Ignatius
Background: The aim was to examine the predictability of stage of disease (FEV1 ) and measures of strength (arm and leg) to arm and leg ergometry capacity of patients with chronic respiratory diseases. Methods: A total of 44 chronic respiratory disease patients, 16 males and 28 females (mean age = 59.8 ± 11.9 years), with an FEV1 of 22%–89% predicted (mean FEV1 % predicted = 54.6 ± 18.3) participated. All participants completed spirometry, Medical Research Council grade, anthropometric assessment, submaximal arm and leg ergometry testing, grip strength, and isokinetic quadriceps and hamstrings strength and endurance testing. Results: To determine contributing and predictor variables of arm and leg ergometry capacity, multiple linear and binary regression analyses were performed. Multiple regression analysis demonstrated that quadriceps strength (N m), FEV1 % and grip strength (kg) predicted 64% of peak wattage during submaximal leg ergometry testing (adjusted R 2 = 64%, F = 26.387 and p = 0.00). Quadriceps strength showed the highest predictability of peak leg ergometry wattage ( p = 0.00, β = 0.844 and t = 6.238), followed by grip strength and FEV1 % ( p = 0.038, β = −0.270 and t = −2.143 and p = 0.028, β = −0.230 and t = 2.279, respectively). A second regression analysis determined that quadriceps strength (N m), FEV1 % and grip strength (kg) predicted 53% of peak wattage during submaximal arm ergometry testing (adjusted R 2 = 0.53, F = 17.018 and p = 0.00). Quadriceps strength was the only independent variable that showed predictability of peak arm ergometry wattage ( p = 0.00, β = 0.793 and t = 5.125). The odds ratio analysis indicated that chronic respiratory disease patients with high quadriceps strength have 13.76 times higher odds of having high peak arm ergometry wattage. This odds ratio equated to an 85% probability of having high arm ergometry peak wattage if quadriceps strength is high. Conclusions: In summary, the main factors predicting leg ergometry capacity were quadriceps strength, FEV1 and grip strength. Quadriceps strength was the only statistically significant predictor of peak arm ergometry wattage, suggesting a relationship between arm and leg functionality in chronic obstructive pulmonary disease patients.